2008
DOI: 10.1111/j.1471-4159.2007.05063.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of receptor internalization in the agonist‐induced desensitization of cannabinoid type 1 receptors

Abstract: Agonist‐induced internalization of G protein‐coupled receptors (GPCRs) is an important mechanism for regulating signaling transduction of functional receptors at the plasma membrane. We demonstrate here that both caveolae/lipid‐rafts‐ and clathrin‐coated‐pits‐mediated pathways were involved in agonist‐induced endocytosis of the cannabinoid type 1 receptor (CB1R) in stably transfected human embryonic kidney (HEK) 293 cells and that the internalized receptors were predominantly sorted into recycling pathway for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
81
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 99 publications
(89 citation statements)
references
References 38 publications
4
81
0
1
Order By: Relevance
“…In accordance with these reports and our expectation, our study revealed that HG stimulated the levels of CB 1 R proteins in rat mesangial cells. Similar to other G proteincoupled receptors, CB 1 R is internalized following protracted agonist exposure (50), and internalized receptors are predominantly sorted into the recycling pathway for reactivation (62). To determine whether HG activates CB 1 R and upregulates its expression, we expressed C-terminal GFP-tagged CB 1 R in HEK293 cells, because the transfection efficiency in rat mesangial cells was too low to show the internalization.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with these reports and our expectation, our study revealed that HG stimulated the levels of CB 1 R proteins in rat mesangial cells. Similar to other G proteincoupled receptors, CB 1 R is internalized following protracted agonist exposure (50), and internalized receptors are predominantly sorted into the recycling pathway for reactivation (62). To determine whether HG activates CB 1 R and upregulates its expression, we expressed C-terminal GFP-tagged CB 1 R in HEK293 cells, because the transfection efficiency in rat mesangial cells was too low to show the internalization.…”
Section: Discussionmentioning
confidence: 99%
“…This has been demonstrated in many cell lines, including CHO (Rinaldi-Carmona et al, 1998), AtT20 Jin et al, 1999;Roche et al, 1999), F11 (Coutts et al, 2001), neuroblastoma N18TG2 (Keren and Sarne, 2003) and HEK293 (Keren and Sarne, 2003;Leterrier et al, 2004) cells, as well as in hippocampal neurons, which naturally express CB 1 R (Coutts et al, 2001;Leterrier et al, 2006). According to different studies, this agonist-induced CB 1 R endocytosis occurs via clathrin-and/or caveolin-mediated pathways in different cell types (Bari et al, 2008;Hsieh et al, 1999;Keren and Sarne, 2003;Wu et al, 2008).…”
mentioning
confidence: 91%
“…Potent SNO-mediated inhibition was also observed for lysophosphatidic acid receptors, whereas S-nitrosylation facilitated signaling of muscarinic receptors (Kokkola et al, 2005). By S-nitrosylation of ␤-arrestin, nitric oxide may modify opioid (Bohn et al, 1999(Bohn et al, , 2000(Bohn et al, , 2002Gainetdinov et al, 2004) and cannabinoid (Rubino et al, 2006;Wu et al, 2008) tolerance and dependence. Although not directly demonstrated in the context of S-nitrosylation, it is well accepted that inhibition of neuronal NOS reduces morphine tolerance (Kolesnikov et al, 1993;Elliott et al, 1994), which reflects the dynamics of endocytotic cycling of the receptor between membrane and clathrin coated pits.…”
Section: G Regulation Of G-proteins Involved In Inhibitory Pain Contmentioning
confidence: 99%